The Effect of Sales and Receivables Turnover on Company Net Profit - Mudjiyono Mudjiyono (Journal of Management and Business Environment (JMBE), 2022)
This study aims to find empirical evidence about the influence of sales and receivable turnover on the company's net profit in manufacturing companies listed on the Indonesia Stock Exchange during the period of 2013-2016. The factors tested in this study are sales, receivable turnover, and net income. The method used to select the sample companies in this study was purposive sampling. To test the influence, multiple linear regression at a significance level of 5% with the help of a computer program SPSS version 20.0 for Windows was applied. Based on the partial test results (t test), sales has a significant effect on the company's net profit with a positive direction, while the receivable turnover has no significant effect on net income.